Thinking Beyond Neoliberalism
XIII, 268 p. 1 illus.
Keywords: “The volume offers an interesting range of perspectives on future possibilities beyond the present and the aftermath of neoliberalism. It is of interest to students, academics, and activists concerned with radical social and political transformation in contemporary societies.” –Gerard Delanty, Professor of Sociology and Professor of Social and Political Thought, University of Sussex, UK “This collection convenes contributions aiming to analyse, fight, and overcome the most threatening danger for humankind and democracy today: neoliberalism. The contributors make clear that there are arenas of struggle and resistance, spaces of hope, and actors invested in an emancipatory trajectory against the neoliberal processes of marketisation and commodification that leave the world in the hands of racketeers who are responsible for the unimaginable wealth of the few, and the extreme poverty of the many.” –Heinz Sünker, Rudolf-Carnap-Senior-Research-Professor, BergischeUniversität of Wuppertal, Germany “Thinking Beyond Neoliberalism is an excellent volume that moves us beyond the dogmatic confines of neoliberalism to imagine possibilities for transition. The interdisciplinary tone and the fearless attempt to engage with the big questions of our time makes this book essential reading for anyone interested in building a better world.” –Susanne Soederberg, Professor of Global Development Studies, Queen’s University, Canada This book brings together leading academics and activists to address the possibilities for qualitative social change beyond neoliberalism, providing introductory essays on alternative societies, transition, and resistance. Bringing together discussions on universal basic income, actually existing communism, parecon, circular economies, workers co-operatives, ‘fully automated luxury communism,' trade unionism, and party politics, the volume provides one of the first scholarly interventions to systematically evaluate possibilities for transition and resistance across theoretical, political, and disciplinary traditions. Neal Harris is a Lecturer in Sociology at Oxford Brookes University, UK. Onur Acaroğlu is an Instructor at Bilkent University, Ankara, Turkey, and a co-founder of the Free University of London (FUL), UK.